2020
DOI: 10.1111/sji.12921
|View full text |Cite
|
Sign up to set email alerts
|

IgG‐mediated suppression of antibody responses: Hiding or snatching epitopes?

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 88 publications
1
12
0
1
Order By: Relevance
“…The mechanism of suppression has been controversial, and it was thought that infused antibody simply caused clearance of the foreign antigen preventing access to immune responding cells. However, animal studies point to antigen-specific blockade, such that antibody can “mask” a specific epitope on a single cell or molecule without affecting the response to other antigens [ 22 , 24 , 26 , 27 ]. Blockade or steric interference by passive antibody can potentially inhibit viral antigen binding to cognate B cell receptors during early B cell activation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of suppression has been controversial, and it was thought that infused antibody simply caused clearance of the foreign antigen preventing access to immune responding cells. However, animal studies point to antigen-specific blockade, such that antibody can “mask” a specific epitope on a single cell or molecule without affecting the response to other antigens [ 22 , 24 , 26 , 27 ]. Blockade or steric interference by passive antibody can potentially inhibit viral antigen binding to cognate B cell receptors during early B cell activation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapeutic monoclonal antibodies (mAbs) are utilized to treat a wide variety of disorders, including cancer and autoimmune diseases [83]. After the administration of mAbs, Fcγ receptor (FcγR)-expressing cells, including monocytes, macrophages, neutrophils, and NK cells, can extract mAb-bound cell surface molecules from target cells via trogocytosis, leading to the reduced efficacy of mAb-based therapies [3,84] (Figure 5). As observed in TCR-mediated trogocytosis, FcγR-mediated trogocytosis occurs rapidly (within 1 h), accompanies the transfer of membrane patches, and requires actin polymerization [17,[85][86][87][88].…”
Section: Trogocytosis Triggered By Ligand-receptor Interaction-2: Fcγr-mediated Trogocytosismentioning
confidence: 99%
“…In line with this observation, it has been reported that excess Ab could lead to the suppression of the Ab response in vivo [24]. A possible explanation is epitope masking, in which Abs may hide the epitopes of Ags from B cells or other Abs [25]. Nevertheless, the mechanism behind the Ab‐mediated immunosuppression remains unclear, especially in pathological conditions such as malignant disease.…”
Section: Discussionmentioning
confidence: 84%